E-WOM BEHAVIOUR MELALUI SOCIAL NETWORKING SITE: SOCIAL CAPITAL DAN HOMOPHILY SEBAGAI ANTESEDEN - Elfitra Azliyanti (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2020)
This research aims to investigate the intention to respond issues of ‘megathrust’ in West Sumatera, through social networking sites. An empirical study conducted to analyse the linkage of social capital, homophily, and e-wom behaviour towards attitude and intention to response. Social capital comprises two factors, bonding social capital and bridging social capital. Quantitative technique analysis was utilized to examine five hypotheses through a survey designed on the Likert five point scale. The sampling technique of this research is purposive sampling. Data was obtained from 157 respondents who were directly having read the news about the earthquake disaster issues of ‘Megathrust’ in West Sumatera through social networking sites. Questionnaire online via link of my3q was used to collect data. The influence among determinant factors were analysed at the level of second-order constructs using SmartPLS 2.0 M3 software. The results showed that homophily not been a concern to determine the intentions of individual response, but more influenced by other antecedents, namely social capital, e-wom and attitude toward issues.